Company Size Moderates the Effect of Real Earning Management and Accrual Earning Management on Value Relevance - Sistya Rachmawati (ETIKONOMI, 2019)
The purpose of this study is to determine the effect of real and accrual earnings management on the value relevance, proxied by predictive value, feedback value and timeliness. Furthermore, this study investigates whether the company size variable can strengthen the effect of real and accrual earning management on value relevance. Multiple regression models are used with secondary data between 2014-2016 from 61 companies, resulting in 183 observations. The results show that there are positive effects of accrual earnings management on predictive value and feedback value and adverse effect on timeliness. Meanwhile, real earnings management only has a positive effect on predictive value. On the other hand, company size only strengthens the effect of accrual earnings management on timeliness.JEL Classification: G39, M41